2001
DOI: 10.1152/ajpheart.2001.281.6.h2473
|View full text |Cite
|
Sign up to set email alerts
|

Altered leptin signaling is sufficient, but not required, for hypotension associated with caloric restriction

Abstract: Caloric restriction of mammals leads to decreases in blood pressure and heart rate. Although relevant clinically, the mechanisms involved, in terms of hormones and signaling pathways invoked, are currently not known. Circumstantial evidence suggests that leptin signaling may be involved with the bradycardia and hypotension associated with caloric restriction. This hypothesis was specifically tested using leptin-deficient mice (ob/ob) or leptin-receptor rats (Koletsky). Ob/ob mice were hypertensive during the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 33 publications
3
47
1
Order By: Relevance
“…In several studies BP was evaluated 48 h after surgery, a time-frame not sufficient for stabilizing BP and day/night circadian rhythm. In contrast to previous findings but more according to our data, Swoap reported slightly increased blood pressure in ob/ob mice with levels of 108±2 mmHg compared to 100±2 mmHg in controls [32]. In that study, BP was also measured by telemetry like in ours.…”
Section: Discussioncontrasting
confidence: 99%
“…In several studies BP was evaluated 48 h after surgery, a time-frame not sufficient for stabilizing BP and day/night circadian rhythm. In contrast to previous findings but more according to our data, Swoap reported slightly increased blood pressure in ob/ob mice with levels of 108±2 mmHg compared to 100±2 mmHg in controls [32]. In that study, BP was also measured by telemetry like in ours.…”
Section: Discussioncontrasting
confidence: 99%
“…Seven mice were anesthetized initially with 5% isoflurane in an oxygen stream and maintained on 1-2% isoflurane. Mice were kept on a heating pad (38°C) throughout implantation of the blood pressure telemeter (PAC20; Data Sciences International) in the left common carotid artery (24). Implantation of the blood pressure telemeter into the abdominal aorta of seven rats (PAC40; Data Sciences International) was performed as described previously (24).…”
Section: Animalsmentioning
confidence: 99%
“…Mice were kept on a heating pad (38°C) throughout implantation of the blood pressure telemeter (PAC20; Data Sciences International) in the left common carotid artery (24). Implantation of the blood pressure telemeter into the abdominal aorta of seven rats (PAC40; Data Sciences International) was performed as described previously (24). Mice and rats were maintained on a heating pad for 48 h after the surgery and then housed individually at 30°C for 1 wk to allow time for recovery.…”
Section: Animalsmentioning
confidence: 99%
“…Studies in rat kidneys have shown that the brush border membranes of CR animals had decreased content of several phospholipids (phosphatidylserine, phosphatidylcholine, phosphatidylethanolamine, and sphingomyelin) and cholesterol (44). In addition to modulating renal lipid metabolism, other mechanisms may be involved in CR effects on age-related renal disease, such as modulating BP, which definitely plays an important role in the progression of renal disease (45)(46)(47)(48).…”
Section: Role Of Altered Lipid Metabolism In Renal Diseasementioning
confidence: 99%